Labour flows in Hungary in 2002-2021 based on a comprehensive set of administrative data - Levente Erdélyi; Lajos Tamás Szabó (Magyar Nemzeti Bank, 2024)
In our study, we present the job-to-job, hire and separation rates from 2002 to 2021 based on the comprehensive, anonymous database of the Hungarian State Treasury. We filtered out the distortions in the administrative data, for example company reorganisations, from the labour flows. Job-to-job rates occurred procyclical over the 20 years, while the rate of entries and exits responds less to the cyclical state of the economy. By different characteristics, the rates are heterogeneous in terms of level and dynamics. The regional pattern of entry and exit rates remains stable over time and correlates with the development of districts. There is no difference in cyclicality by gender, but men change jobs more frequently than women. Job transitions have a diminishing chance, as the age increases, and job-to-job flows of the younger age group are also more sensitive to economic conditions. Employees in jobs requiring lower qualifications are more likely to change jobs. The flows between firm size categories are mostly the highest within the same size category. Large companies have the lowest turnover rate relative to the number of employees.
Keywords: J21; J61; J62; 330; labour flows; job-to-job rates; worker characteristics